Pengaruh varietas dan konsentrasi broth kulit pisang sebagai media alternatif pertumbuhan Aspergillus niger - Nucky Istiqomah Mulyawati; Deny Utomo; Muh. Aniar Hari Swasono (Fakultas Pertanian Universitas Yudharta Pasuruan, 2019)
Banana is an influential agriculture commodity in Indonesia, for consuming the fruit or making use of the leafs and steam, with high demand of banana fruit, there’s also left with tons of peel waste. Banana peel waste which usually contain cellulose (35 %–50 %), hemicellulose (25 %–30 %), and lignin (25 %–30 %). The fruit peel wastes containing sugars that are metabolized by microorganisms which make the potential of microbiology growth. Aspergillus niger as one of influental fungi for industrial can be used on production of α-Amylase. The experimental design used was Completely Randomized Design factorial with two factors. Factor I is Banana peel variety, with 4 level which contain ( Ambon Banana Peel, Kepok Banana Peel, Raja Banana Peel and Candi Banana Peel. Factor II is broth media concentration with 3 level ( 2gr banana peel : 100ml Aquadest ; 4gr banana peel : 100ml Aquadest; 6gr banana peel : 100ml Aquadest) with the result 12 combinations with 3 repeat. The result of the streak will be observed for seven days. The result of analysis will be analyzed with Analysis of Variance (ANOVA), if there’s a significant result, the analysis will be continued to LSD test 5%. The result of research pointed that variance of banana peel and concentration of broth media did show significant difference according to ANOVA result on day one until seven. Best variance of treatment found in V2K3 (Kepok Banana Peel with 6gr / 100ml concentration) resulted with average diameter reaching 55mm.